2000
DOI: 10.1111/1468-2362.00044
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic and Stochastic Beta and Its Implications in Global Capital Markets

Abstract: This article investigates the dynamic and stochastic behaviour of the beta coefficient of the one-factor international capital asset pricing model (ICAPM), and its implications for the pricing of stock markets at the country level and the forecasting of stock returns in global stock markets. We apply several novel econometric techniques and conduct necessary statistical tests. We find that the ICAPM has a stochastic and dynamic beta coefficient and that the global stock market is efficient and integrated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 82 publications
(160 reference statements)
0
16
1
2
Order By: Relevance
“…(2000) investigan el comportamiento dinámico y estocástico del coeficiente beta de un factor único en un modelo internacional de activos de capital (ICAPM), y sus consecuencias para los precios de los mercados de valores a nivel de los países y la predicción de rendimientos en los mercados bursátiles mundiales. Lin así como Lin (2000) encuentran que el ICAPM tiene un coeficiente beta estocástico y dinámico, que el mercado mundial de acciones es eficiente e integrado, y el portafolio es eficiente en el sentido de la relación media-varianza.…”
Section: Revisión De Literaturaunclassified
See 1 more Smart Citation
“…(2000) investigan el comportamiento dinámico y estocástico del coeficiente beta de un factor único en un modelo internacional de activos de capital (ICAPM), y sus consecuencias para los precios de los mercados de valores a nivel de los países y la predicción de rendimientos en los mercados bursátiles mundiales. Lin así como Lin (2000) encuentran que el ICAPM tiene un coeficiente beta estocástico y dinámico, que el mercado mundial de acciones es eficiente e integrado, y el portafolio es eficiente en el sentido de la relación media-varianza.…”
Section: Revisión De Literaturaunclassified
“…Los resultados mostrados en páginas previas indican, a diferencia de Lin y Lin (2000), que el mercado mexicano de capitales no está plenamente integrado al mercado internacional de capitales ya que son estadísticamente significativos los coeficientes beta tanto del factor de riesgo internacional como el correspondiente al factor local. Es conveniente destacar también que, en forma similar al estudio de Lin y Lin (2000), nosotros encontramos que las alfas son negativas o no estadísticamente significativas, lo que refuerza el hecho de que considerando coeficientes betas variables el mercado, es condicionalmente eficiente considerando un modelo condicional de valuación de activos de capital.…”
Section: Conclusionesunclassified
“…A great number of studies have also been devoted to testing the Unbiasedness hypothesis (Lin & Chen, 1998;Lin, 1999;Lin & Lin, 2000& Lin et al,2002 provide thorough reviews of this empirical literature. Many of the studies in this area have considered only one sample period, one time horizon (mostly one month), and one or more currencies, so that the rejection or acceptance of the Unbiasedness hypothesis may well depend on the sample periods, currencies, and time horizons under study (Lin, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…All the above‐cited risk measures assume that the risk of securities has a predictable fixed value, and consequently Beta is also considered as a deterministic value. Recently, many researchers mentioned that Beta may vary with time (Lin and Lin, ) and several authors tried to find the link between the Beta and other uncertain macroeconomic variables such as asset changes, financial leverage, dividend changes, inflation rate, real income, and growth rate (Chen, ). Mitchell and Pulvino () reported that an investor, who is ready to pay $30 for an asset when the market return is high, may reject to pay $25 for the same asset when the market is performing badly.…”
Section: Introductionmentioning
confidence: 99%